Isabel de Valois, a hope for peace against the heresy. Topics of the epithalamium in the Christian "oratio" (1560) written by Pedro del Frago - Serrano Cueto, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2012)
This paper offers a Latin poem written by Pedro del Frago, conceived like a Christian oratio, to celebrate Isabel de Valois’ arrival in Spain (1560). That poem is as a pretext for doing long annotations in which the author defends the Council of Trent and the Catholic struggle against the heresy. Frago has also introduced some topics of the epithalamium in the poem, perhaps under the influence of the humanist Diego de Guevara.
Keywords: Pedro del Frago; Isabel de Valois; Neolatin Poetry; The Council of Trent; Epithalamium; Diego de Guevara.